2018
DOI: 10.1007/s00330-018-5510-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of T2-W MR imaging and diffusion-weighted imaging for the early post-treatment local response assessment of patients treated conservatively for cervical cancer: a multicentre study

Abstract: Objectives To compare MR imaging with or without DWI and clinical response evaluation (CRE) in the local control evaluation of cervical carcinoma after radiotherapy. Methods In a multicentre university setting, we prospectively included 107 patients with primary cervical cancer treated with radiotherapy. Sensitivity and specificity for CRE and MR imaging (with pre-therapy MR imaging as reference) (2 readers) were evaluated using cautious and strict criteria for identifying residual tumour. Nested logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A 10-center study of 272 patients with breast cancer demonstrated that ADC changes after 12 weeks of neoadjuvant chemotherapy was predictive of a complete pathologic response (30). However, a three-center study, with differences in protocols between centers, did not find additional diagnostic value in ADC changes in cervical tumors following radiation therapy (31). The importance cle) increase in ADC in those with residual disease may be used independently of other clinical factors (duration of platinumfree interval, number of previous lines of therapy) to identify response and to indicate longer progression-free survival (PFS).…”
Section: Association Of Adc All Change With Pfs and Overall Survivalmentioning
confidence: 99%
“…A 10-center study of 272 patients with breast cancer demonstrated that ADC changes after 12 weeks of neoadjuvant chemotherapy was predictive of a complete pathologic response (30). However, a three-center study, with differences in protocols between centers, did not find additional diagnostic value in ADC changes in cervical tumors following radiation therapy (31). The importance cle) increase in ADC in those with residual disease may be used independently of other clinical factors (duration of platinumfree interval, number of previous lines of therapy) to identify response and to indicate longer progression-free survival (PFS).…”
Section: Association Of Adc All Change With Pfs and Overall Survivalmentioning
confidence: 99%
“…It has been widely reported the application of DWI to evaluate the therapeutic effect in cervical cancer, breast cancer, and colorectal cancer. 8 - 10 Research has shown that the increase in the ADC value was related to the decrease in tumorous cellular density after effective treatment. 11 Before CRT, esophageal cancer with high tumor cell proliferation, high cellularity, decreased extracellular volume, cell membrane barrier, and increased absorption of protein to water molecules all districted the diffusion of water molecules and decreased the ADC value of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DWI coupled with T2W images can improve the evaluation of various gynecological cancers. A prediction model was constructed combining both sequences to evaluate parametrial invasion (PMI) in cervical cancer [31]; DWI significantly increases the specificity of MR imaging in the detection of residual tumor compared with T2W images alone in cervical cancer after radiotherapy [32,33]. For endometrial cancer, the depth of myometrial invasion and the presence of lymph node metastasis are important prognostic factors.…”
Section: Discussionmentioning
confidence: 99%